Design and Synthesis of Hepatitis C Virus NS3 Protease Inhibitors - Johansson, Anja (Uppsala universitet, Avdelningen för organisk farmaceutisk kemi, 2003)
Hepatitis C Virus (HCV) is the leading cause of chronic liver disease worldwide as well as the primary indication for liver transplantation. More than 3% of the world’s population is chronically infected with HCV and there is an urgent need for effective therapy. NS3 protease, a viral enzyme required for propagation of HCV in humans, is a promising target for drug development in this area. This thesis addresses the design, synthesis and biochemical evaluation of new HCV NS3 protease inhibitors. The main objective of the thesis was the synthesis of peptide-based protease inhibitors of the bifunctional full-length NS3 enzyme (protease-helicase/NTPase). Three types of inhibitors were synthesized: i) classical serine protease inhibitors with electrophilic C-terminals, ii) product-based inhibitors with a C-terminal carboxylate group, and iii) product-based inhibitors with C-terminal carboxylic acid bioisosteres. The developmental work included the establishment of an improved procedure for solid-phase peptide synthesis (SPPS) in the N-to-C direction, in contrast to the C-to-N direction of classical SPPS methods. This inverse method facilitated synthesis of the peptides modified at the C-terminal. The potency of more than seventy newly synthesized inhibitors was assessed in an in vitro assay using the native form of the protease, i.e. the full-length NS3. The structure-activity relationship (SAR) data achieved was different from SAR data obtained from the more widely used truncated NS3 (protease domain) assay, indicating that the helicase domain of NS3 participates in the binding of the inhibitors. The most potent inhibitors identified in this study contained a C-terminal phenyl acyl sulfonamide moiety, i.e. a carboxylic acid bioisostere. It is concluded that the acyl sulfonamide moiety is a promising P1-P1´ spanning entity, which may have potential for use in the development of more drug-like HCV protease inhibitors.